A technological approach towards integrated solid waste management in developing countries - Lozano Garcia, Ana Maria (2017)
This research is grounded in the planning concept of Integrated Solid Waste Management (ISWM). ISWM was developed to promote sustainability in the waste management for developing countries. Waste managers and policy makers in developing countries have been adopting the principles of ISWM into their waste strategies for several decades. But despite their many efforts, still important problems remain, as is the case of low collection coverage, lack of proper treatment of the different waste types, high dependency on final disposal sites and even in some cities uncontrolled dumping is still accepted as the only way to handle the waste. For that reason, waste management in developing countries needs to adopt new managerial visions and implement new technical solutions to provide a more sustainable and effective service. To do so, governments, waste managers, policy makers need to focus all their efforts in doing very well informed decisions when planning or improving their waste strategies. The main aim of this thesis, was to study the concept of ISWM from the technology point of view, and proceed with the adjustment of “Compendium of Sanitation Systems and Technologies (CSST) 2nd revised edition” (Tilley et al., 2014) within the framework of ISWM. CSST is a well-known planning tool in the field of sanitation for developing countries to manage waterwaste and excreta. So that in this thesis, the structure of CSST was adjusted for the management of solid waste. The research was carried out using as a research method ‘qualitative content analysis’, whereby public reports issued by relevant international organizations in the field of waste management were analyzed to construct the structure of the new compendium of ISWM. As result, the new compendium of ISWM contains a robust structure composed by: five (5) functional groups (or waste services), thirty-tree (33) sanitation technologies and thirty-five (35) products (inputs/outputs). This tool can be used either as a planning tool, communication tool or as a simple source of inspiration to contemplate the most suitable technological options and what they have to offer. The structure here presented is meant as well, to invite other researchers interested in waste management to continue the process of adjustment of CSST for solid waste management, to provide the field with a new source for planning or improving waste systems in developing countries.